Factors Affecting Sustainability Among Employees of Private Banks in South Jakarta - Kayla, Viona; Emilisa, Netania; Agustia , Anggita; Herliyani , Rani; Pasha, Nabeel Ariq (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Sustainability is now a strategic priority for private banks. In line with international guidelines, sustainable investment trends, and commitments to achieving the Sustainable Development Goals (SDGs), they are now integrating Environmental, Social, and Governance (ESG) principles into risk assessment, consumer preferences, and service development. Due to ESG integration, business objectives must be aligned with global commitments to biodiversity and climate. They also strengthen the bank's business model by incorporating social and environmental responsibility into long-term value creation. This study aims to examine the influence of digital transformation, entrepreneurship, and digital innovation on sustainability among employees of private banks in South Jakarta. This study applies a descriptive quantitative method with a sample of 120 respondents. The sampling technique uses purposive sampling methodology. Data collection used a questionnaire with a 1–5 Likert scale. Then, a Structural Equation Model (SEM) was used to analyze the data. The results showed that digital transformation and entrepreneurship had a positive and significant impact on digital innovation, as well as a positive impact on sustainability. In addition, it has been proven that digital innovation partially mediates the impact of digital transformation and entrepreneurship on sustainability. Overall, the success of improving sustainability in private banks is influenced by the effectiveness of digital transformation and entrepreneurial orientation supported by digital innovation, in line with respondents' perceptions that the four variables have been implemented quite well in their work environment.